KETERLIBATAN AYAH DALAM PEMENUHAN GIZI BALITA DI DUSUN TUWIRIÂ DESA SEDURI KECAMATAN MOJOSARI MOJOKERTO - Ratnaningsih, Tri (JURNAL KEPERAWATAN BINA SEHAT, 2016)
While this is still a lot of fathers who have not understood the importance of their role in the growth of the children one of them in terms of fulfilling the needs of nutrition or nutrition for toddlers, where they still do not understand about proper nutrition for their children serving food that fit and appropriate to the age of the child. The purpose of the study to identify the involvement of fathers in fulfillment nutrition of child’s under five yearsin Tuwiri village of Seduri Mojosari Mojokerto. The design of this research was descriptive. The research population was whole father who have a child’s under five years in Tuwiri village of Seduri Mojosari Mojokerto as many as 42 people. Samples taken with the total sampling tevhniques. Data collected by questionnaire and processed in editing, coding, scoring, and tabulating, then presented and processed by editing, coding scoring and tabulating. Then presented in the form of frequency distribution table. The results of this study showed most respondents by negative in the fulfillment of child nutrition as much as 22 respondents (52,4%). This shows that the majority of respondents are still many who have not been engaged towards the fulfillment of child’s nutrition. This is happens because of most of dads prefer to earn a living. Expected respondents can improve the information received about the way the fulfillment of the toddler nutrition by means of reading a magazine or a newspaper, look at televition on and listen to the guidance so that although the father did not have enough time but the father can still meet the nutritional needs of children.Key Words : Involvement Of Fathers, Nutrition, child’s under five years